Mapping Review of Individuals Who are Bilingual with Autism Spectrum Disorders - Yllades, Valeria; Pierson, Lauren; Bowman-Perrott, Lisa; Dunn, Claudia (Journal of the American Academy of Special Education Professionals, 2022)
This systematic mapping review summarized findings from 54 studies focused on individuals who are bilingual with autism spectrum disorders (ASD). Currently, there is a scarcity of research, which provides strategies for this population. The purpose of this study was to review literature to provide information, both qualitative (narrative) and quantitative (research studies) about the outcomes for intervention, the issues faced with this population, and identify best practices. The current review encompassed research for 725 participants’ ages 2 to 35 years old. Findings indicated that the majority of the studies, 28, were concerned with issues and interventions for this population. The remaining articles, 26, reported on bilingual exposure on language delay, although no significant results for language delay were found based on bilingual exposure, and parent beliefs regarding their children with ASD.